Research on the mechanisms of natural products in radiation protection - Li, Xiaoxue; Yu, Luyao; Xu, Hongchi; Xing, Xiaowen; Wu, Wenhui; Feng, Yifei; Ma, Li; Zhou, Zheng; Li, Bailin; He, Ying (Frontiers in Bioengineering and Biotechnology, 2025)
Radiation exposure initiates a cascade of reactions, including the release of reactive oxygen species, DNA double-strand breaks, and cellular apoptosis, leading to cell death, tissue damage, and potentially the development of cancer. Consequently, there is an urgent need to develop highly effective and low-toxicity radioprotective agents. Traditional chemically synthesized protective agents face significant limitations in clinical applicability due to their pronounced off-target toxicity, narrow therapeutic window, and high production costs. In recent years, bioactive natural compounds, including polysaccharides, polyphenols, saponins, alkaloids, and peptides, have emerged as key research targets for the next-generation of radioprotective drugs due to their low toxicity and multi-target synergistic effects. Notably, each class of compounds demonstrates distinct characteristics in its mechanisms of action. In comparison to synthetic drugs, these natural compounds exert protective effects primarily through three mechanisms: antioxidant activity, anti-apoptotic effects, and immune modulation. Additionally, they offer advantages such as abundant availability and high safety profiles. Current research must further elucidate the mechanisms of action of their active ingredients to establish a theoretical foundation for radiation protection in contexts involving radiation workers and potential nuclear emergencies. This article systematically elucidates the molecular mechanisms underlying radiation damage, summarizing the multidimensional protective effects and action pathways of natural products. Its objective is to provide both a theoretical foundation and technical insights for the development of novel radioprotectants.